Changing research trends in seed responses to stresses: a bibliometric analysis over the last 50 years - Liu, Zhouli; Qi, Lin; Hu, Benyang; Zhao, Yuchen; Wang, Hetong; Zhang, Nan; Duan, Xiangbo; Li, Binglun; Xin, Mingran; Zhong, Sihui; Liu, Hengyu (Frontiers in Plant Science, 2026)
IntroductionAbiotic stresses (e.g., drought, salinity, heavy metals) intensified by global environmental changes threaten plant seed germination, seedling establishment, and population persistence. Elucidating the spatio-temporal dynamics and adaptive mechanisms of seed stress responses is critical for ecological conservation and stress-resistant crop breeding, yet long-term global and regional research trends lack systematic integration.MethodsA bibliometric analysis was conducted using CiteSpace v.6.4.R1 to process 15,627 literature records (9,042 from Web of Science; 6,585 from CNKI) spanning 1975–2024, focusing on publication dynamics, cooperation networks, intellectual base, research hotspots, and emerging frontiers.ResultsSeed-stress research evolved through three stages (initial exploration, rapid growth, steady breakthrough), with WOS and CNKI seeing annual increases of 684 and 453 articles post-2020. China led in WOS publication volume, but cooperation networks showed low connectivity. International high-cited literature centered on salinity/oxidative stress (80% reviews), while domestic research focused on staple crop stress responses and practical indicators. Post-2020, international frontiers leaned toward nanomaterials and signal transduction, and domestic frontiers prioritized cadmium pollution control and germination regulation.DiscussionGlobal research presents a diverse, integrated landscape, while domestic research exhibits strong application orientation with relative fragmentation. Future research should integrate basic mechanisms with practical needs, strengthen interdisciplinary/international collaboration, and focus on combined stress adaptation and green regulatory technologies, providing theoretical and technical support for enhancing plant stress resistance and ecological security.